2018
DOI: 10.1108/ijdi-04-2018-0058
|View full text |Cite
|
Sign up to set email alerts
|

The trade integration and Pakistan’s export performance

Abstract: Purpose The purpose of this study is to investigate the effect of trade integration on Pakistan’s export performance (value of exports, number of exporters and number of products per exporter) during 2003 to 2010. Design/methodology/approach Data from the World Bank Exporters Dynamics Database are analysed using fixed effect panel data techniques. Findings The results suggest that trade integration with South Asian Free Trade Area (SAFTA), China and Iran play remarkable role in improving export value by 73… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…The coefficient obtained from PPML also confirms the positive association of PMFTA with the vegetable exports of Pakistan, though with a lower magnitude in comparison with OLS and FE estimations. Our results are consistent with the findings of (Alam, 2018). Pakistan's trade agreements with China, Afghanistan, Sri Lanka, and Malaysia show consistently positive and significant coefficients across various estimations.…”
Section: Resultssupporting
confidence: 94%
“…The coefficient obtained from PPML also confirms the positive association of PMFTA with the vegetable exports of Pakistan, though with a lower magnitude in comparison with OLS and FE estimations. Our results are consistent with the findings of (Alam, 2018). Pakistan's trade agreements with China, Afghanistan, Sri Lanka, and Malaysia show consistently positive and significant coefficients across various estimations.…”
Section: Resultssupporting
confidence: 94%
“…Two approaches commonly used to examine the impact of FTAs are gravity models (Abidin et al, 2013;Ahmed et al, 2021;Alam, 2015;Ali et al, 2020;Anderson & Yotov, 2016;Dianniar, 2013;Didia et al, 2015;Guan & Sheong, 2020;Hayakawa et al, 2016;Herath, 2014;Lopez, 2019;Mahabir et al, 2020;Urata & Okabe, 2007) and computable general equilibrium (CGE) models (Kartini & Margaret, 2020;Kustiari & Hermanto, 2017;Muchopa et al, 2020;Nekhay et al, 2020;Phat & Hanh, 2019;Rosyadi & Widodo, 2018;Tsutsumi et al, 2019). Bekkers & Rojas-Ramagosa (2018) compared these two models and found that they have distinct advantages while showing a certain degree of convergence in the literature.…”
Section: Methodsmentioning
confidence: 99%
“…However, further discussion is needed to explore the role of globalization in the halal food trade, particularly in international trade issues such as trade agreements among countries. Urata & Okabe (2007) examine the impact of FTAs on total trade using the gravity model, while Alam (2015) explores the impact of FTAs on Pakistan's export performance. Several FTA variables include the South Asian Free Trade Area (SAFTA), Bilateral-China, Bilateral-Malaysia, Bilateral-Sri Lanka, Bilateral-Mauritius, and Bilateral-Iran.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although China is an exporter of textiles and apparel to more than 209 countries, the Chinese market is flooded with textiles and apparel from Indonesia. The data for textile export and manufactured export are collected from UN COMTRADE Statistics from World Integrated Trade Solution (WITS) provided by World Bank (Alam, 2018) The strength of the Chinese economy is seen from the total export number of 2,263,370,504.30 in thousands of US $ and total imports 1,843,792,938.80 in thousands of US $, this can be called the Chinese trade balance leading to a positive trade balance 419,577,565.51 in thousands of US $ Trade growth of 2.43% compared to world growth of 1.50% (WITS). While India had a total export of 294,364,490.16 in thousands of US $ and total imports of 444,052,353.84 in thousands of US $, until the end of 2017 the Indian trade balance was negative (149,687,863.67) in thousands of US $.…”
Section: Introductionmentioning
confidence: 99%